Contribution à l’Amélioration de quelques activités PGP par mutagénèse - MEDJAHED, Saadia (My University, 2022)
Plant Growth-Promoting Rhizobacteria (PGPR) can form an associative symbiosis with plants, which results in stimulation of plant growth. PGPR harbour different phytobeneficial mechanisms (non-symbiotic nitrogen fixation, phytohormone synthesis, etc.). The objective of the present study is the improvement of some PGP activities in the two strains of Stenotrophomonas maltophiliaa NHA68 and NHA78 by physical mutagenesis with UV rays at different exposure times (0, 5, 10, 15, 20, 25 and 30 mins). After mutation, a high improvement in AIA production was observed in mutant strains NHA68-m18 and NHA78-m5, and a strong improvement in phosphate solubilization in mutant strains NHA68-m18, NHA68-m20, NHA68 -m17, NHA78- m14, NHA78-m4, NHA78-m12 and NHA78-m19
Keywords: PGPR; Stenotrophomonas maltophiliaa; enhancement; mutation; UV